2023
DOI: 10.3389/fpls.2023.1293186
|View full text |Cite
|
Sign up to set email alerts
|

Boosting grapevine breeding for climate-smart viticulture: from genetic resources to predictive genomics

Gabriele Magon,
Valeria De Rosa,
Matteo Martina
et al.

Abstract: The multifaceted nature of climate change is increasing the urgency to select resilient grapevine varieties, or generate new, fitter cultivars, to withstand a multitude of new challenging conditions. The attainment of this goal is hindered by the limiting pace of traditional breeding approaches, which require decades to result in new selections. On the other hand, marker-assisted breeding has proved useful when it comes to traits governed by one or few genes with great effects on the phenotype, but its efficac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 141 publications
0
3
0
Order By: Relevance
“…In view of the drastic climate change and its impact on grapevine yield and quality, efforts have been undertaken to capitalize on the rapid advancements in genomic technologies to face current and future environmental challenges. These efforts aim to uncover significant associations between the rich grapevine diversity of indigenous varieties and a wide range of valuable agronomic traits at the molecular level [ 168 , 178 ]. In addition, grapevine performance relies intensely on appropriate rootstock utilization.…”
Section: Application Of New Genomic Technologies In Landraces and Ind...mentioning
confidence: 99%
See 1 more Smart Citation
“…In view of the drastic climate change and its impact on grapevine yield and quality, efforts have been undertaken to capitalize on the rapid advancements in genomic technologies to face current and future environmental challenges. These efforts aim to uncover significant associations between the rich grapevine diversity of indigenous varieties and a wide range of valuable agronomic traits at the molecular level [ 168 , 178 ]. In addition, grapevine performance relies intensely on appropriate rootstock utilization.…”
Section: Application Of New Genomic Technologies In Landraces and Ind...mentioning
confidence: 99%
“…In recent years, a great number of targeted or GWAS studies have been reported aimed at dissecting the genetic basis underlying key traits related to grapevine quality and stress resilience [ 168 , 178 ]. One of the most important traits of the grape table and raisin industry is seedlessness.…”
Section: Application Of New Genomic Technologies In Landraces and Ind...mentioning
confidence: 99%
“…In recent years, several innovative approaches have been developed for the identification and selection of resilience alleles ( Magon et al., 2023 ; Villalobos-López et al., 2022 ), enabling a deeper understanding of the genetic basis of resilience in various organisms. Transcriptomics have played a crucial role.…”
Section: Modern Approaches For the Identification And Selection Of Re...mentioning
confidence: 99%